Transformation of Papuan Independence Values: Looking at the Conflict in Papua through Post-secular Society Perspective - Yotam Senis; Dwia Aries Pulubuhu; Suparman Abdullah; Sakaria Sakaria (Faculty of Social and Political Sciences - UIN Walisongo Semarang, 2025)
The evolution of Papuan independence values illustrates a historical transition from traditional cosmological beliefs, linking freedom to ancestors, land, and nature, to modern political aspirations. Influences from missionary education, colonial governance, and contemporary political systems have reshaped these values, leading to the rise of ethnonationalist consciousness. This study aims to analyze how traditional religious conceptions of freedom shifted toward demands for political sovereignty within a post-secular social context. A qualitative exploratory approach was applied, using expert interviews with traditional leaders, religious figures, youth leaders, activists, and government officials in Manokwari and Jayawijaya, complemented by literature review and NVivo-assisted coding. The findings show that traditional religious values—expressed through rituals such as koreri—were secularized and reinterpreted as political symbols. This transformation strengthened Papuan ethnonationalism and contributed to prolonged conflict, especially after dissatisfaction with Penentuan Pendapat Rakyat (PEPERA) and the emergence of movements such as OPM. The study implies that understanding the Papuan conflict requires acknowledging the spiritual foundations of political aspirations.